2015
DOI: 10.1177/1931243115580231
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: Principles of American journalism: An introduction

Abstract: When researching quotes on history, you will find many that say history can and should serve as teaching examples for today and for the future. As professors, what we appreciate most about this book is that it intertwines history with the core teachings of journalism. While other texts with this connection exist, the current book authors teach through their writing. For example, when describing what democracy needs from journalism, the authors use three metaphors for the role of the press, namely, the mirror, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Boyle et al (2004) found the more a protest’s goals or tactics go against the status quo, the more likely media coverage is to be negative and marginalizing. For example, Black civil rights, immigrants’ rights, and indigenous rights movements historically have been and continue to be marginalized in the mainstream media (Baylor, 1996; LaPoe & LaPoe, 2018; Mourão et al, 2021). In contrast, while feminist movements at first are marginalized and ridiculed, eventually the media present them as non-threatening to the status quo (Robinson, 1978), in part because they are viewed as frivolous or unthreatening (Ashley & Olson, 1998).…”
Section: Protest Paradigmmentioning
confidence: 99%
“…Boyle et al (2004) found the more a protest’s goals or tactics go against the status quo, the more likely media coverage is to be negative and marginalizing. For example, Black civil rights, immigrants’ rights, and indigenous rights movements historically have been and continue to be marginalized in the mainstream media (Baylor, 1996; LaPoe & LaPoe, 2018; Mourão et al, 2021). In contrast, while feminist movements at first are marginalized and ridiculed, eventually the media present them as non-threatening to the status quo (Robinson, 1978), in part because they are viewed as frivolous or unthreatening (Ashley & Olson, 1998).…”
Section: Protest Paradigmmentioning
confidence: 99%